Практичні аспекти управління якістю при формуванні бізнес-моделі підприємства ресторанного господарства - Гросул, Вікторія Анатоліївна; Іванова, Тетяна Павлівна (НТУ "ХПІ", 2016)
У статті досліджено сутність основних категорій управління якістю. Визначені основні критерії управлінні якістю послуг на підприємствах ресторанного господарства. Сформовано систему параметрів оцінки якості послуг підприємства ресторанного господарства. Розроблено інтегровану модель впливу якості послуг підприємства ресторанного господарства на критерії результативності діяльності. Обґрунтовано методичний інструментарій комплексної оцінки якості послуг підприємств ресторанного господарства. Результати досліджень можуть бути використані при побудові системи управління якістю на підприємствах ресторанного господарства.

The article discusses the theoretical and practical aspects of service quality management at the enterprises of restaurant economy. The evolution of the concept of "quality" and defines the essence of the main categories of quality management. The features of the nature of production at the enterprises of restaurant economy. It was found that when assessing the quality of the restaurant business enterprises should take into account all four stages of the expansion of production: production, distribution, exchange and consumption. The result of this study is to assess the parameters of the system formed at enterprise restaurant management services to meet customer requirements. Developed an integrated model of the impact of the quality of restaurant management enterprise services on the criteria of efficiency of its activity. Practical significance has developed methodological tools integrated assessment of the quality of services of restaurant business enterprises. The proposed approach is based on building patterns, and allows you to evaluate the quality of the restaurant business, enterprise services for the main criteria, taking into account the priority needs and demands of consumers. The research results can be used in the construction of quality management system in enterprises restaurant business, as well as in management decisions to transform the existing business model.
Practical aspects of quality when forming business model enterprise restaurant business
Keywords: якість; виробництво; продукція; обслуговування; послуга; управління; підприємство; ресторанне господарство; quality; manufacturing; production; maintenance; service; enterprisess of restaurant business